Phenotypic Variation in Desert Teak Tecomella undulata - Chakravarty, A K; Chand, Gyan (Annals of Arid Zone, 2016)
Variation of corolla colour plant, height, diameter at breast height and collar diameter of plants, length of capsule, number and weight of seeds per capsule was observed in a 10 year old plantation of Tecomella udulanta Seem. Corolla colour, was found to vary from yellow 'to red with intermediate shades. Considerable variation was observed in the quantitative characters studied. 1here seems to be good scope for selection of plants on the basis of diameter at breast. height of plants.